2013
DOI: 10.1007/s00384-013-1808-4
|View full text |Cite
|
Sign up to set email alerts
|

Increase in colonic diverticulosis and diverticular hemorrhage in an aging society: lessons from a 9-year colonoscopic study of 28,192 patients in Japan

Abstract: Colonic diverticulosis and diverticular bleeding are prevalent and increasing in Japan. Given the significant association of age with this trend, both diseases can be expected to increase for decades to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
122
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 38 publications
6
122
4
Order By: Relevance
“…During the period from 1960 to the 1980s, Kubo et al [13] reported that the prevalence of colonic diverticula was only 8.9% among patients who underwent barium enema examination. Since the 1990s, the prevalence of div erticulosis seen on barium enema examination or colonoscopy has increased to 15%25% [5,14] . In addition, more than 80% of patients who had diverticulosis were elderly.…”
Section: Comparison Of Specific Diseases In Eg and Lgmentioning
confidence: 99%
See 2 more Smart Citations
“…During the period from 1960 to the 1980s, Kubo et al [13] reported that the prevalence of colonic diverticula was only 8.9% among patients who underwent barium enema examination. Since the 1990s, the prevalence of div erticulosis seen on barium enema examination or colonoscopy has increased to 15%25% [5,14] . In addition, more than 80% of patients who had diverticulosis were elderly.…”
Section: Comparison Of Specific Diseases In Eg and Lgmentioning
confidence: 99%
“…In addition, more than 80% of patients who had diverticulosis were elderly. Diverticulosis is thus thought to increase with aging [5] . As the absolute number of diverticula in colonic diverticulosis increases with the aging of the population, the risk of DH is increased.…”
Section: Comparison Of Specific Diseases In Eg and Lgmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, opportunities to treat patients with colonic diverticular disease (diverticular bleeding and diverticulitis) have been increasing in recent years as the prevalence of colonic diverticula has increased [1,2]. In particular, the number of reports of colonic diverticular bleeding from Japan has been increasing in the past 2 or 3 years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as increase of colon diverticulosis [3-5], CDB incidence appears to be increasing in both western and eastern countries [5-8]. CDB is characterized as arterial bleeding, which is caused by the rupture of vasa recta penetrating through diverticula [9].…”
Section: Introductionmentioning
confidence: 99%